Appendix 4.5: Citizenship of Justice Claudio Teehankee Sr. - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
In 1982, the justices of the Supreme Court resigned in toto because chief justice Enrique Fernando had authorized the adjustment of the bar exam score of Gustavo Ericta, son of justice Vicente Ericta, thus giving the younger Ericta a passing mark. Majority of the justices—even constant dissenter Justice Claudio Teehankee Sr.—were reinstated. However, the issue of Teehankee’s citizenship—which had cropped up before when he was to be appointed by Ferdinand Marcos as undersecretary in the department of justice—was resurrected while Teehankee’s reappointment was in process. After resolving the issue twice before, the issue was raised again, apparently by Marcos himself, when Teehankee was up for consideration for the position of chief justice given his seniority (see Reed 1985). This suggests that Marcos was perfectly comfortable with Teehankee being the Court’s token dissenter, but he could not tolerate having the Court’s primus inter pares be an opponent of his regime.